Morphological features of the comorbid course of non-alcoholic steatohepatitis on the background of obesity and secondary arterial hypertension. - Khukhlina, O. S.; Antoniv, A. A.; Kuzminska, O. B.; Mandryk, O. Ye.; Kotsiubiichuk, Z. Ya. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Non-alcoholic fatty liver disease is the most common chronic liver disease in developed countries (ranging from 17 to 33%), and non-alcoholic steatohepatitis is found in 2-3% of the general population. In the initial examination of patients, 30-40% of patients with non-alcoholic steatohepatitis have fibrosis of the liver, which is a natural result of chronic liver diseases. Objective. The aim of the study was to find out the morphological characteristics of the nonalcoholic steatohepatitis in patient with the comorbid obesity and secondary arterial hypertension in comparison with the isolated course of non-alcoholic steatohepatitis by comparing the morphological characteristics of non-alcoholic steatohepatitis depending on the presence of secondary arterial hypertension. Methods. 140 patients with non-alcoholic steatohepatitis were examined: 70 patients with non-alcoholic steatohepatitis and obesity of I degree (1 group), 70 patients with comorbid course of non-alcoholic steatohepatitis, secondary arterial hypertension and obesity of the 1st degree (group 2). A transcutaneous or target biopsy of the right lobe of the liver was performed in 35 of the examined patients; in 18 cases were obesity of 1st degree and 17 cases obesity of the 1st degree and secondary arterial hypertension. Results. As a result of the study, it was found that in patients with comorbid course of obesity and non-alcoholic steatohepatitis with secondary arterial hypertension increases the degree of steatosis, the degree of balloon, hyaline-droplet dystrophy, dystrophic changes in hepatocytes. Conclusion. The comorbid course of non-alcoholic steatohepatitis with secondary arterial hypertension is characterized by a significantly higher histological activity, which leads to the progression of fibrotic changes in the liver.